Misdiagnosis: Acute Chest Syndrome That Evolved into Acute Respiratory Distress Syndrome in a Patient without a Documented History of Hemoglobinopathy - Christoph Sossou; Ogechukwu Chika-Nwosuh; Christopher Nnaoma; Jose Bustillo; Asad Chohan; Etinosasere Okundaye; Pratik Patel (Case Reports in Medicine)
Acute chest syndrome (ACS) is a feared complication of sickle cell disease. Here is a case of a patient who presented with symptoms suggestive of acute chest syndrome yet had a delayed diagnosis presumably due to the lack of documented history of sickle cell disease of the patient, consequently evolving into acute respiratory distress syndrome (ARDS). He was subsequently diagnosed with heterozygous sickle cell SC disease on hemoglobin electrophoresis. After appropriate management with mechanical ventilator, broad-spectrum empiric intravenous antibiotics, exchange transfusion, and intravenous fluid resuscitation, the patient was medically optimized and safely discharged home, with significant improvement noted on successive follow-up visits.